FENOMENA PERDAGANGAN PEREMPUAN DALAM FIKSI JAWA MODERN - Darni Darni (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe woman trafficking practice in modern Javanese fiction. Woman trafficking was analyzed based on the ideology and causes using New Historicism theory. The findings show that woman trafficking experienced by the characters in all of the stories is the same. They are deceived by procurers and sold as prostitutes in Indonesia and abroad. There are three causes of womantrafficking, i.e. a view looking down on women, woman dependency, and women’s poverty and low education. The stories of woman trafficking support feminism more. Women as victims of woman trafficking can get freedom and autonomy. Feminism ideology is also supported by men. The male characters help the female characters release themselves from woman trafficking by accepting them as their partners.